Estudio de caso: Funcionamiento del sistema familiar de un adolescente con conducta punible (2019)
In the present work the relationship between the punishable behavior of a 15-year-old adolescent with family functioning is established, since several studies have taken place, where the behaviors of adolescents are described in a larger scale as a result of family functioning. Since there in these homes are to abound the intra-family violence, the low economic resources, rigid or lax parental styles, the lack of opportunities, conflicting relationships between parents and children etc.